Surface microstructure and texture evolution during interrupted annealing in ultra low carbon steels - Gautam J.; Petrov R.; Kestens L.A.I.; Leunis E. (My University, 2025)
The austenite-to-ferrite phase transformation, which is an inherent feature of low-alloyed ultra low carbon steels, has scarcely been investigated to control surface texture and microstructure evolution. This paper investigates the systematic evolution of texture and microstructure at the metal-vapour interface during interrupted annealing in vacuum. Interrupted annealing experiments were carried out on three ultra low carbon steel sheets alloyed with Mn, Al and Si. The texture and microstructures have been investigated by X-ray diffraction and SEM-EBSD techniques. These results reveal a very clear variation in the surface texture components as well as in the surface microstructure after BCC recrystallisation and double α-γ-α transformation interrupted annealing. The recrystallisation texture consists mainly of a <111>//ND fibre, while the transformation texture at the surface exhibits a <100>//ND fibre in combination with components of the <110>//ND fibre. It has been revealed that the latter specific surface texture was present in a monolayer of outer surface grains which were in direct contact with the vapour atmosphere. This observed phenomenon could be explained by considering the role of surface energy anisotropy occurring during phase transformation annealing. © (2010) Trans Tech Publications.